Role of Myeloperoxidase in Patients with Chronic Kidney Disease - Kisic, Bojana (Oxid Med Cell Longev, 2016)
Chronic kidney disease (CKD) is a worldwide public health problem. Patients with CKD have a number of disorders in the organism, and the presence of oxidative stress and systemic inflammation in these patients is the subject of numerous studies. Chronic inflammation joined with oxidative stress contributes to the development of numerous complications: accelerated atherosclerosis process and cardiovascular disease, emergence of Type 2 diabetes mellitus, development of malnutrition, anaemia, hyperparathyroidism, and so forth, affecting the prognosis and quality of life of patients with CKD. In this review we presented the potential role of the myeloperoxidase enzyme in the production of reactive/chlorinating intermediates and their role in oxidative damage to biomolecules in the body of patients with chronic kidney disease and end-stage renal disease. In addition, we discussed the role of modified lipoprotein particles under the influence of prooxidant MPO intermediates in the development of endothelial changes and cardiovascular complications in renal failure.